Masseter muscle and gingival tissue inflammatory response following treatment with high-fructose corn syrup in rats: Anti-inflammatory and antioxidant effects of kefir - Ekici, Omer; Aslan, Esra; Aladag, Tugce; Guzel, Hilal; Korkmaz, Omer Adil; Bostanci, Aykut; Sadi, Gokhan; Pektas, Mehmet Bilgehan (WILEY-HINDAWI, 2022)
The aim of the study was to evaluate whether high-fructose corn syrup (HFCS) intake (20% beverages) impacts antioxidative structures and inflammation in the gingival tissue and masseter muscle of rats. Kefir was tested for its potential utility on changes induced by HFCS. Animals were randomly divided into four groups as control, kefir, HFCS, and HFCS plus kefir. HFCS was given as 20% solutions in drinking water while kefir supplementations were given by gastric gavage for 8 weeks. It has been clearly determined that the HFCS diet increased expressions of interleukin (IL)-6, IL-1 beta, and tumor necrosis factor-alpha proinflammatory structures via lymphocyte infiltration by suppressing antioxidant enzymes such as catalase, superoxide dismutase, and glutathione peroxidase in both tissues. Kefir improved these undesirable changes in rats fed with HFCS. The results of this current study, the first investigation to examine the effects of kefir on masseter muscle and gingival tissue, may provide new access to the restorative effects of kefir consumption on oral health disorders caused by high fructose in the diet. Practical applications In this study, at an early age, the effects of kefir on improving inflammation via antioxidation in the masseter muscle and gingival tissue were investigated for the first time. We showed that kefir feeding ameliorates lymphocyte infiltration on the high-fructose corn syrup (HFCS)-induced masseter muscle and gingival tissue inflammation in rats. The mRNA expressions of inflammatory parameters measured in the study were supported by protein measurements via ELISA or immunohistochemistry. In the present study, kefir may play an important role in the antioxidation and inflammation process on the masseter muscle and gingival tissue against HFCS.
Keywords: antioxidants; gingiva; HFCS; inflammation; kefir; masseter muscle; LACTOBACILLUS-CASEI; OXIDATIVE STRESS; CONSUMPTION; DYSFUNCTION; Biochemistry & Molecular Biology; Food Science & Technology